3, 5 and 13 Motte Street, November 11, 1898 - Boston Elevated Railway Company (Tufts Archival Research Center, 2005)
Elevated view east of (left to right) 13, 5 and 3 Motte Street, located between Washington Street to the west-northwest and Harrison Street to the east-southeast. Signage and a street light adorn the facade of 13 Motte Street, which is included along the left side of the photograph. Its facade faces south-southwest. (Left to right) 5 and 3 Motte Street are located along the south-southwest elevation of 295 Harrison Street, which is visible along the right side of the photograph. Two men stand on the sidewalk lining the north-northeast side of Motte Street. Copyprint 9 x 7 5/16 Photographs